Web context and the multiple semantic linguistic origins and its impacts on the prophet’s text - Yousef A. Baker, El-Ebiary; Omar, Md Din; Abdul Ghani, Md Din (2020)
The web content control system is an integrated software package that constitutes a system for managing the content to be published and displayed for visitors and members of the site, and it provides tools to control the publishing process, and these systems usually work on the Internet, although they can also be run on the local network. So, This research aims to apply a linguistic study of the phenomenon of multiplicity of semantics and linguistic meanings to some of the words mentioned in the Prophet’s Hadith, and the extent of the influence of this semantic multiplication in determining the meaning of the prophetic text, and whether or not it is based on a separation in a legal rule of worship or not, with an attempt to weight between multiple and different meanings and meanings, Clarification of weightings, to the conclusion that linking semantic linguistic studies with Islamic studies through analyzing their texts and explaining their linguistic phenomena; One of the important and useful studies in human research, and the research will follow the descriptive analytical method, as the research chose some words from the hadith of the Prophet, as its meanings and linguistic origins multiplied, so he analyzed them and returned them to their semantic linguistic origins used by the Arabs, then applied those indications to the word in the context of the Prophet’s text, And the explanations of the meanings and meanings indicated by those contexts, then weighting between the different meanings and indications in accordance with the linguistic and legal principles, and among the results of the research that the linguistic studies have a close link to the legal studies, and that the multiple semantic assets may have a significant impact in determining the meaning of the hadith, And it is based on determining the different legal rule of worship in it.